HUBUNGAN MOTOR ABILITY DENGAN KETERAMPILAN TEKNIK FUTSAL (DRIBBLING) PADA TIM FUTSAL SPARTA FC PEKANBARU - Gunawan, Muara; Juita, Ardiah; S, Wedi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: This research aims to determine the relationship between the motorability test and the dribbling ability in futsal games on the Sparta FC Pekanbaru FutsalTeam. Hypothesis testing resulted in a relationship between the motor ability test andthe dribbling ability of the Sparta FC Pekanbaru Futsal Team. The sequence ofactivities carried out so that conclusions can finally be drawn is as follows: (1) amotorbike ability test was held on the Sparta FC Pekanbaru futsal team as a totalsample with the aim of making the participants' dribbling abilities known, (2) adribbling test was held to see the ability of the Sparta FC team Based on the resultsobtained, it shows the relationship between motor ability and futsal technical skills(dribbling). After carrying out the motor ability test with the dribbling test, the SpartaFC Pekanbaru Futsal Team received a motor ability test with 5 test stages. The SpartaFc Pekanbaru Futsal Team shows that the level of motor ability tests carried out by theSparta FC Pekanbaru Futsal Team shows that there is a relationship between the basictechnical skills of futsal dribbling. According to the Product Moment correlationanalysis, rx.y = 0.692 > r table: 0.553, which means "Motor ability (X1) has asignificant effect on dribbling technique. Meanwhile, the results of the correlationanalysis are significant or not.Keywords: Motor Ability, Futsal Technique (Dribbling)